Phoberus sulcatus (Thunberg, 1787) sensu lato: in-depth morphological analysis of male genitalia reveals three cryptic species (Coleoptera: Scarabaeoidea: Trogidae) - Strümpher, Werner P.; Huchet, Jean-Bernard; Costa-Silva, Vinícius Da (Zootaxa, 2025)
In this study, we conducted a comprehensive review of the widely distributed keratin-beetle species Phoberus sulcatus (Thunberg, 1787) (Trogidae). Based on the examination of over 1,200 specimens across its entire known distribution range, we identified three distinct species within Phoberus sulcatus sensu lato. Consequently, Trox instabilis Haaf, 1953 is removed from synonymy with Phoberus sulcatus and formally transferred to the genus Phoberus MacLeay, 1819. Both species are redescribed and diagnosed. In addition, we describe a new species, Phoberus erwinhaafi Strümpher, sp. nov. The three species are allopatric and presently have non-overlapping distributions. Specifically, Phoberus sulcatus is confined to the Eastern Cape, KwaZulu-Natal, the southeastern part of the Northern Cape and the eastern part of the Western Cape provinces. The revalidated and recombined Phoberus instabilis (Haaf, 1953) is widespread, occurring in Botswana, Lesotho, throughout the central and eastern interior of South Africa, and Zimbabwe. Phoberus erwinhaafi Strümpher, sp. nov., represents geographically distinct populations in Namibia and South Africa’s Northern Cape province. The distributions of all three species are mapped, and a neotype is designated for the missing type specimens of Trox sulcatus (originally described as Throx sulcatus). We also include an erratum correcting an error in Strümpher & Stals (2021).